Magnesium-aluminum-silicon transparent microcrystalline glass and preparation method thereof

By optimizing the raw material composition and heat treatment process of magnesium-aluminum-silicon crystalline glass, magnesium-aluminum-silicon transparent microcrystalline glass with high hardness, fracture toughness and high transmittance were prepared, which solved the problem of difficulty in taking into account both chemical strengthening and optical performance in the prior art, and achieved high-performance microcrystalline glass suitable for protective materials of electronic equipment.

CN119528440APending Publication Date: 2025-02-28CHANGSHU JIAHE DISPLAY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411459813.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing magnesium aluminum silicon crystal crystallized glasses take into account high hardness, fracture toughness and high transmittance, and it is difficult to achieve ideal chemical strengthening and optical properties.

Method used

By optimizing the raw material composition and heat treatment process, a magnesium-aluminum-silicon transparent microcrystalline glass with high crystallinity has a composition content of 45-68% SiO2, 16-35% Al2O3, 5-15% MgO, etc., and the overflow method or float molding, annealing and crystallization treatment are used to control the precipitation of crystals and the optical properties of the glass.

Benefits of technology

It has achieved high hardness (Vickers hardness greater than 780kgf/mm²), high fracture toughness (fracture toughness greater than 1.0MPa/m2), high transmittance (visible light transmittance greater than 91% at 0.6mm thickness) and good chemical reinforcement effects, and is suitable for protective materials for electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528440A_ABST
    Figure CN119528440A_ABST
Patent Text Reader

Abstract

The invention discloses magnesium-aluminum-silicon transparent microcrystalline glass and a preparation method thereof, the crystallinity of the microcrystalline glass is greater than or equal to 65%, and the crystalline phase of the microcrystalline glass comprises at least one of cordierite, Mg < 0.6 > Al < 1.2 > Si < 1.8 > O < 6 >, MgAL2Si4O12, spodumene and Li < x > Al < x > Si < 3-x > O < 6 >; the Vickers hardness is greater than 780 kgf / mm; the fracture toughness is greater than 1.0 MPa / m < 2 >; the elastic modulus is greater than 88Gpa; and under the thickness of 0.6 mm, the transmittance in the visible light wavelength range is greater than or equal to 91%, and the haze is less than 0.2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microcrystalline glass, and in particular relates to a magnesium aluminum silicon transparent microcrystalline glass and a preparation method thereof. Background Art

[0002] With the rapid update and iteration of electronic wearable devices, glass materials / microcrystalline glass materials have become the main materials for electronic devices. It is difficult for existing materials to simultaneously take into account high hardness, high fracture toughness and high transmittance while meeting chemical strengthening requirements. For example, the fracture toughness of transparent microcrystalline glass is greater than 1MPa / m 2 , but the transmittance is not high enough; or the elastic modulus and hardness are high, but it cannot be chemically strengthened well, or the chemical strengthening strength value is limited. This is because: in order to better chemically strengthen the microcrystalline glass, a small amount of alkali metal must be introduced into the mother glass design as an ion exchanger, and lithium oxide, as a special alkali metal oxide, will affect the precipitation of crystals during the crystallization process of magnesium-aluminum-silicon system microcrystalline glass heat treatment, resulting in the risk of difficult to control crystallization and a decrease in transmittance, and it is impossible to obtain ideal high-strength crystals and high-transparency glass.

[0003] The Chinese patent with patent publication number CN113735450A discloses a transparent high-hardness magnesium-aluminum-silicon glass-ceramic, whose raw materials are composed of the following components: SiO2, MgO, Al2O3, Li2O, ZnO, ZrO2, P2O5, CeO2, SnO2, Sb2O3. The invention also provides a method for preparing the above-mentioned transparent high-hardness magnesium-aluminum-silicon glass-ceramic, including the following steps: uniformly mixing the raw materials, heating up to obtain melted glass liquid; pouring the melted glass liquid into a preheated mold for molding, demolding after cooling, then annealing, and then cooling to room temperature; cutting the obtained annealed glass into glass slices, and grinding and polishing; after cutting into the required specifications, nucleation treatment is performed to obtain transparent high-hardness magnesium-aluminum-silicon glass-ceramic. The transparent high-hardness magnesium-aluminum-silicon glass-ceramic of the present invention is a high-transmittance, high-strength magnesium-aluminum-silicon glass-ceramic suitable for use on the surface of smart phones. Although Li is added in the technical solution disclosed in this patent, the introduction of Li2O glass heat treatment results in surface crystallization, that is, there are crystals only on the surface of the glass but no crystals inside. Although the glass has good transmittance, the haze is large and the optics cannot meet the usage requirements. Summary of the invention

[0004] In order to overcome the deficiencies in the prior art, the present invention proposes a magnesium aluminum silicate transparent microcrystalline glass and a preparation method thereof, and further proposes a magnesium aluminum silicate microcrystalline glass with ion exchange chemical strengthening, which solves the above-mentioned problems in the prior art. The technical solution of the present invention is as follows: The first embodiment of the present invention is: a magnesium aluminum silicon transparent microcrystalline glass, the crystallinity of the microcrystalline glass is ≥65%, and the crystal phase contains cordierite, Mg 0.6 Al1.2 Si 1.8 O6、MgAl2Si4O 12 , spodumene, Li x Al x Si 3-x At least two of O6; Vickers hardness greater than 780kgf / mm²; fracture toughness greater than 1.0MPa / m 2 ; Elastic modulus is greater than 88Gpa; At a thickness of 0.6mm, its transmittance in the visible light wavelength range is ≥91%, and the haze is less than 0.2.

[0005] The microcrystalline glass has the following composition in percentage by mass: 45-68% SiO2, 16-35% Al2O3, 5-15% MgO, 0.2-6% ZnO, 0.1-4% B2O3, 1.5-7% Li2O, 0.5-5% Na2O, 0-4% K2O, 0.1-5% TiO2, 2-8% ZrO2, 0.1-4% P2O5, 0.1-6% Y2O3, 0.1-2%HfO2, 0.1-5%Ta2O5, 0.1~1.5%La2O3 and 0.1-0.5%Sb2O3.

[0006] Furthermore, (MgO+ZnO+Y2O3) / (SiO 2+ The mass ratio of MgO / (SiO2+Al2O3) is 0.075~0.40. If the ratio is less than 0.075, cristobalite crystals are likely to appear during the crystallization process, which greatly reduces the glass transmittance and affects the optical properties. At the same time, the crystallinity of the microcrystalline glass is low, which greatly reduces the strength of the microcrystalline glass. If the ratio is greater than 0.40, it will make the crystallization difficult to control and the target crystal cannot be precipitated. Preferably, the mass ratio of MgO / (SiO2+Al2O3) is 0.06~0.28.

[0007] Furthermore, (Li2O+Na2O+ K2O) / (SiO 2+ The mass ratio of Al2O3) is 0.025~0.15. Preferably, the ratio of Li2O / R2O is 0.25-0.8. This is because the introduction of alkali metal R2O, especially Li2O, in the magnesium-aluminum-silicon system will affect the precipitation of microcrystalline glass crystals. When the content is too high, crystallization on the surface of microcrystalline glass will occur. When Li2O / R2O is greater than 0.8, crystallization on the surface of microcrystalline glass will occur during heat treatment, which cannot meet the use requirements, and the glass structure is unstable, and the elastic modulus and hardness cannot meet the requirements. When Li2O / R2O is less than 0.25, the reduction of Li2O will reduce the Na-Li exchange amount in chemical strengthening, and it is impossible to form a larger compressive stress on the glass surface, making the later ion exchange chemical strengthening effect of microcrystalline glass unsatisfactory.

[0008] Furthermore, (ZrO2+TiO2+Ta2O5) / (SiO 2+ The mass ratio of TiO2 / (ZrO2+Ta2O5) is 0.2-2. This is because when TiO2 / (ZrO2+Ta2O5) is lower than 0.2, it is difficult for the glass to precipitate ideal crystals, and there is a risk of crystallization on the surface of the glass. When TiO2 / (ZrO2+Ta2O5) is higher than 2, the glass is easily devitrified by heat treatment, and the base glass is yellowish in color.

[0009] A method for preparing a magnesium aluminum silicon transparent microcrystalline glass, comprising the following steps: raw material preparation, mixing, melting, cooling, overflow molding or float molding, annealing treatment, and crystallization treatment, wherein the melting temperature is 1520-1580°C and the melting time is 10 hours; the annealing temperature is 550-650°C and the time is 4 hours; the raw material composition is: 45-68% SiO2, 16-35% Al2O3, 5-15% MgO, 0.2-6% ZnO, 0.1-4% B2O3, 1.5-7% Li2O, 0.5-5% Na2O, 0-4% K2O, 0.1-5% TiO2, 2-8% ZrO2, 0.1-4% P2O5, 0.1-6% Y2O3, 0.1-2%HfO2, 0.1-5%Ta2O5, 0.1~1.5%La2O3, 0.1-0.5%Sb2O3.

[0010] Furthermore, the crystallization treatment is divided into two stages, the temperature of the first stage is 630-720°C, and the time is 4-10h; the temperature of the second stage is 750-920°C, and the time is 1-2h.

[0011] The second scheme of the present invention is: the microcrystalline glass obtained by the first scheme is strengthened, and the strengthening process is: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h, and after strengthening, the surface compressive stress is greater than 400Mpa, CS50 is greater than 170MPa, DOL is greater than 150 microns, and the tensile stress density line is greater than 40000MPa / mm; at a thickness of 0.6mm, the whole face of the 2.5D sample falls from a height of 1.8m without damage, the height of the 120g ball drop is greater than 1.2m, and the four-point bending strength is greater than 700MPa. The elastic modulus is greater than 88GPa, HV is greater than 780, KIC is greater than 1, and the transmittance of the 0.6mm thick microcrystalline glass at 550nm is greater than 91%, and the haze is less than 0.2.

[0012] The functions of each substance in the present invention are as follows: SiO2 is an essential component of the glass of the present invention, forming a glass network structure and improving chemical stability and thermal stability. If the SiO2 content is below 45wt%, the glass forming properties and chemical stability will deteriorate, and it will be easy to separate into phases, or even fail to form glass. Therefore, the lower limit of the SiO2 content is preferably above 45wt%, more preferably above 48wt%. If the SiO2 content is above 68wt%, the melting temperature is high, clarification and homogenization are difficult, and it is not conducive to the chemical strengthening of the glass, and the impact and drop resistance of the strengthened microcrystalline glass material will be reduced. Therefore, the upper limit of the SiO2 content is preferably 68wt%, more preferably 63wt%.

[0013] Al2O3 is an essential component of the glass of the present invention, forming a glass network structure, which is very beneficial for improving the glass structure and chemical stability. It can refine the grains and control the crystallization rate during heat treatment, which is beneficial for chemical strengthening of microcrystalline glass to improve the ability of ion exchange and enhance the elastic modulus of glass. If its content is less than 18wt%, it is difficult to control the crystallization rate, the crystal size becomes larger, and the elastic modulus of the glass material decreases. It has a greater impact on the chemical strengthening depth and stress size, especially CS50 and CS80. Therefore, the lower limit of the Al2O3 content is 16wt%. On the other hand, if the Al2O3 content exceeds 35wt%, the melting of the glass becomes difficult, which hinders the precipitation of crystals.

[0014] MgO is an essential component of the composition of the present invention. It belongs to the network exosome, helps to improve the glass material, reduce the melting temperature, and improve the chemical stability. It can be used as the main component of the crystal, and can improve the elastic modulus in the base glass. It can also refine the grains and improve the optical properties during the crystallization heat treatment stage. When the content is low, the target crystal cannot be precipitated. In order to achieve the effect of the present invention, the lower limit of the MgO content is preferably 3wt%, more preferably 4wt%, and further preferably 5wt%; when the content is too high, it will affect the chemical strengthening Na-Li exchange effect, especially the chemical strengthening DOL. The failure to precipitate ideal crystals after crystallization will affect the mechanical properties and optical properties. Therefore, the upper limit of the MgO content is 15wt%, and the preferred upper limit is 13wt%.

[0015] ZrO2 is a necessary component in the present invention, and its main functions are: first, it is used as a crystal nucleating agent to make the glass crystallize uniformly, and can effectively control the precipitation of crystals and the size of crystals to avoid the influence of excessive crystal size on optical properties; second, it can improve the chemical stability of the matrix glass or microcrystalline glass under the condition of high Li content; third, it can improve the hardness and elastic modulus of the glass. It was found in the experimental research process that ZrO2 can also effectively reduce the risk of devitrification of the matrix glass during the forming process. In order to achieve the effect of the present invention, the lower limit of the ZrO2 content is preferably 2wt%, more preferably 3wt%, and further preferably 4wt%; but if too much ZrO2 is contained, the melting temperature of the glass is increased, making melting difficult, and too high will inhibit the precipitation of the target crystal phase, making crystallization uncontrollable. Therefore, the upper limit of the ZrO2 content is 8wt%, and the preferred upper limit is 6wt%.

[0016] TiO2 is the main nucleating agent of the composition of the present invention, which effectively promotes the precipitation of the entire crystal, makes the crystallization controllable, and easily precipitates nano-scale crystal particles, making the microcrystalline glass transmittance higher. The lower limit of the TiO2 content is preferably 0.5wt%, more preferably 1.5wt%, and further preferably 2wt%; but if too much TiO2 is contained, crystallization is uncontrollable, and the risk of devitrification is likely to occur, and the mechanical properties of the microcrystalline glass will be reduced. In addition, too much TiO2 is likely to cause the glass color to be yellowish, affecting the chromaticity. Therefore, the upper limit of the TiO2 content is 5wt%, preferably 3.5wt%, and more preferably 2.5wt%.

[0017] Ta2O5 is a necessary component in the present invention, and its main function is to be used as a nucleating agent. First, it can make the glass crystallize evenly, refine the grain size to produce nano-scale grains, and effectively improve the crystallinity of the glass. Second, as a colorless nucleating agent, it can effectively reduce the yellowing problem of glass caused by the addition of TiO2. When the content is low, nano-scale grains cannot be produced. The lower limit is 1wt%, preferably 2wt%. When the content is too high, the mother glass will undergo phase separation, making crystallization uncontrollable and increasing the risk of glass devitrification. Therefore, the upper limit of Ta2O5 is 5wt%, preferably 4wt%, and more preferably 3wt%.

[0018] As one of the nucleating agents of the present invention, La2O3 helps to reduce the crystallization temperature of cordierite and avoids the precipitation of high-expansion quartz. A small amount of addition will increase the fracture toughness of the glass. When the content is high, the glass has the risk of surface crystallization. Therefore, the La2O3 content is 0.1~1.5wt%.

[0019] P2O5 is an important component in the present invention. It is a glass network former with good nucleation ability. The introduction of a small amount of P2O5 can promote the dissolution of ZrO2 in the glass, reduce the melting temperature, and reduce glass melting defects. However, if the content exceeds 4wt% in this composition, the base glass will produce phase separation. Therefore, the upper limit of P2O5 is 4wt%, preferably 3%, and more preferably 2wt%.

[0020] Na2O is an essential component in the present invention. As the outer body of the glass network, Na2O mainly plays the role of breaking the network to provide free oxygen, lowering the melting temperature, and having a strong inhibitory effect on crystal precipitation. When chemically strengthened ion exchange is performed, the chemical strengthening level is further improved. If the glass contains too much Na2O, the glass expansion coefficient becomes larger, the thermal stability is poor, annealing becomes difficult, and the risk of explosion is prone to occur. It also inhibits the precipitation of crystals, thereby reducing the strength of the microcrystalline glass material. Therefore, the upper limit of the Na2O content is 5wt%, and the preferred upper limit is 3.5wt%.

[0021] Li2O is an essential component in the present invention, which belongs to the outer body of the glass network, plays the role of breaking the network and participating in crystallization, effectively reduces the viscosity of the matrix glass, is conducive to melting, and can reduce the defects of glass bubble stripes. It plays an important role in ion exchange chemical strengthening, and can increase the surface stress value and ion exchange depth of the glass. If its content is less than 1.5wt%, on the one hand, it is not conducive to the glass melting effect, and on the other hand, it is difficult to obtain the ideal ion exchange chemical strengthening level, and it is difficult to ensure the strength of the glass after strengthening. Therefore, the lower limit of the Li2O content is 1.5wt%, and the preferred lower limit is 2wt%. If the Li2O content is too high, the chemical stability of the glass deteriorates, and the chemical strengthening tensile stress density line is too large. At the same time, the mechanical properties of the basic glass decrease, and the glass has the risk of devitrification. It will be difficult to control during crystallization and it will be impossible to precipitate ideal crystals. Therefore, the upper limit of the Li2O content is 7wt%, preferably 5wt%, and further preferably 4.5wt%. The present invention adopts ZrO2, TiO2, Ta2O5 composite nucleating agent and the introduction amount of appropriate Li2O, which effectively reduces the situation of crystallization on the glass surface.

[0022] ZnO can improve the material and thermal properties of the matrix glass, help refine the grains during the crystallization process, improve the optical properties of the microcrystalline glass, reduce the high temperature viscosity of the glass, help eliminate bubbles, and improve the chemical resistance of the glass. The preferred lower limit is 0.2wt%. In this composition, ZnO exists as zinc-oxygen tetrahedrons with a loose network structure. When the content is too high, the elastic modulus and hardness of the glass decrease. Therefore, the upper limit of the ZnO content is preferably 6wt%, and the preferred upper limit is 4.5wt%.

[0023] B2O3 acts as a network former to fill in the network and increase the strength of the glass structure. A small amount of boron oxide can lower the melting temperature. Too high a content can cause phase separation of the glass, affect the optical properties and even cause devitrification. The usage is 0.1-4wt%.

[0024] Y2O3, as an additive oxide component in the present invention, exists in the glass as a network filler, mainly to enhance the hardness and elastic modulus of the glass. Low content also has a good fluxing effect. When the content is high, it will inhibit the precipitation of the target crystal, participate in the crystal formation itself, and affect the transmittance of the microcrystalline glass. The usage amount is 0.1-6wt%.

[0025] HfO2, as an additive oxide component in the present invention, is a network exosome in the glass. After crystallization, it forms a face-centered cubic lattice solid solution that exists in the glass network, which can significantly improve the hardness and wear resistance of the glass. The usage amount is 0.1-2wt%.

[0026] Sb2O3 acts as a clarifier in the present invention, and Sb2O3 is preferably 0.1-0.5wt%.

[0027] The present invention can achieve excellent optical parameters such as full-band transmittance greater than 91%, haze less than 0.2, and Lab-B value less than 0.4 while maintaining high crystallinity through reasonable composition design, and at the same time has the ability to undergo ion exchange chemical strengthening. It can be used as an electronic screen protection material and has good use value. Through the above technical solution, a transparent microcrystalline glass with high hardness, high fracture toughness, and high elastic modulus can be obtained, which solves the problem in the prior art that chemical strengthening, mechanical properties, and optical properties of magnesium-aluminum-silicon system microcrystalline glass cannot be taken into account at the same time, and is suitable for use as an electronic equipment protection material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD pattern of the glass-ceramics crystal prepared in Example 3 of the present invention; Figure 2 This is a crystal morphology diagram of the microcrystalline glass prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] After continuous testing and research, the present invention has controlled the specific composition of the microcrystalline glass material by a crystallization process to generate a crystalline phase with a specified ratio, thereby obtaining the microcrystalline glass material of the present invention at a relatively low cost. In this specification, unless otherwise specified, the content of each component is expressed in terms of weight percentage of the oxide.

[0031] Example 1

[0032] Raw materials (wt%): 48% SiO2; 24.5 Al2O3; 13% MgO; 2.2% Li2O; 4% ZrO2; 3.5% TiO2; 0.4% Na2O; 1% Y2O3; 0.5% P2O5; 0.5% B2O3; 0.2% Sb2O3; 0.5% ZnO; 0.1% K2O; 1.5% Ta2O5; 0.1% HfO2; various raw materials are accurately weighed according to the designed glass composition, the batch materials are fully mixed and stirred, and then put into a platinum crucible and melted at 1560℃ for 24h. After casting, annealing treatment is carried out at 600℃ for 5h and cooling with the furnace. The heat treatment process is as follows: nucleation temperature 660℃, nucleation time 8h, crystallization temperature 800℃, crystallization time 1h, and cooling with the furnace after the heat treatment to obtain microcrystalline glass.

[0033] The main crystal phases of the obtained microcrystalline glass are cordierite, Mg 0.6 Al 1.2 Si 1.8 O6、MgAL2Si4O 12 , elastic modulus is 90GPa, Vickers hardness is 810kgf / mm²; fracture toughness is 1.0MPa / m 2 The transmittance of 0.6mm thick microcrystalline glass at 550nm wavelength is greater than 91%, and the haze is less than 0.15.

[0034] At this time, the impact of a 120g falling ball on the 0.6mm thick microcrystalline glass is less than 0.6m, and the four-point bending strength is 380MPa.

[0035] The microcrystalline glass was further chemically strengthened using the following strengthening process: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h. Its surface compressive stress was measured to be 560MPa, CS50 was greater than 178MPa, DOL was 155μm, tensile stress density line was greater than 41000MPa / mm, 120g falling ball impact resistance for 0.6mm thick glass could reach 1.2m, and four-point bending strength was 760MPa.

[0036] Example 2

[0037] Raw materials (wt%): 50.5% SiO2; 21% Al2O3; 11% MgO; 2% Li2O; 6% ZrO2; 1% TiO2; 1% Na2O; 1.8% Y2O3; 0.5% P2O5; 1% B2O3; 0.2% Sb2O3; 3% ZnO; 0.3% K2O; 0.5% Ta2O5; 0.2% HfO2; Accurately weigh various raw materials according to the designed glass composition, mix the batch materials thoroughly and stir them evenly, then put them into a platinum crucible and melt them at 1560℃ for 24h, after casting and forming, annealing treatment at 600℃ for 5h and cooling with the furnace, the heat treatment process is as follows: nucleation temperature 650℃, nucleation time 8h, crystallization temperature 785℃, crystallization time 1h, after the heat treatment, cooling with the furnace to obtain microcrystalline glass.

[0038] The main crystal phases of the obtained microcrystalline glass are spodumene, Mg 0.6 Al 1.2 Si 1.8 O6, elastic modulus is 88GPa, Vickers hardness is 790kgf / mm², fracture toughness is 1.02MPa / m 2 The transmittance of 0.6mm thick microcrystalline glass at 550nm wavelength is greater than 91%, and the haze is less than 0.10.

[0039] At this time, the impact of a 120g falling ball on the microcrystalline glass with a thickness of 0.6mm is less than 0.5m, and the four-point bending strength is 350MPa.

[0040] The microcrystalline glass was chemically strengthened using the following strengthening process: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h. The surface compressive stress was measured to be 430Mpa, the CS50 was greater than 170MPa, the DOL was 150μm, the tensile stress density line was greater than 41000MPa / mm, the impact of a 120g falling ball on 0.6mm thick glass could reach 1.2m, and the four-point bending strength was 710MPa.

[0041] Example 3

[0042] Raw materials (wt%): 52% SiO2; 28% Al2O3; 5% MgO; 2.5% Li2O; 5% ZrO2; 1.5% TiO2; 1.5% Na2O; 0.1% Y2O3; 2% P2O5; 0.5% B2O3; 0.3% Sb2O3; 1% ZnO; 0.1% K2O; 1.3% Ta2O5; 0.2% HfO2; Accurately weigh various raw materials according to the designed glass composition, mix the batch materials thoroughly and stir them evenly, then put them into a platinum crucible and melt them at 1580℃ for 24h, after casting and forming, annealing treatment at 600℃ for 5h and cooling with the furnace, the heat treatment process is as follows: nucleation temperature 670℃, nucleation time 8h, crystallization temperature 820℃, crystallization time 1h, after the heat treatment, cooling with the furnace to obtain microcrystalline glass.

[0043] The main crystal phases of the obtained microcrystalline glass are spodumene and Mg 0.6 Al 1.2 Si 1.8 O6, the XRD test results of the obtained product are as follows Figure 1 The crystal morphology is shown in Figure 2 As shown, the elastic modulus is 89GPa, the Vickers hardness is 815kgf / mm², and the fracture toughness is 1.04MPa / m 2 The transmittance of 0.6mm thick microcrystalline glass at 550nm wavelength is greater than 91.5%, and the haze is less than 0.06.

[0044] At this time, the impact of a 120g falling ball with a thickness of 0.6mm for the microcrystalline glass is less than 0.5m, and the four-point bending strength is 375MPa.

[0045] The microcrystalline glass was chemically strengthened using the following strengthening process: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h. The surface compressive stress was measured to be 490Mpa, the CS50 was greater than 188MPa, the DOL was 168μm, the tensile stress density line was greater than 43000MPa / mm, the impact of a 120g falling ball on 0.6mm thick glass could reach 1.3m, and the four-point bending strength was 760MPa.

[0046] Example 4

[0047] Raw materials (wt%): 52% SiO2; 25% Al2O3; 8% MgO; 2.5% Li2O; 3% ZrO2; 1.2% TiO2; 1% Na2O; 0.1% Y2O3; 1.5% P2O5; 0.5% B2O3; 0.1% Sb2O3; 1.5% ZnO; 0.1% K2O; 3.3% Ta2O5; 0.2% HfO2; Accurately weigh various raw materials according to the designed glass composition, mix the batch materials thoroughly and stir them evenly, then put them into a platinum crucible and melt them at 1580℃ for 24h, after casting and forming, annealing treatment at 600℃ for 5h and cooling with the furnace, the heat treatment process is as follows: nucleation temperature 655℃, nucleation time 8h, crystallization temperature 775℃, crystallization time 1h, after the heat treatment, cooling with the furnace to obtain microcrystalline glass.

[0048] The main crystal phase of the obtained glass-ceramics is Mg 0.6 Al 1.2 Si 1.8 O6、MgAL2Si4O 12 , Li x Al x Si 3-x O6, elastic modulus is 89GPa, Vickers hardness is 790kgf / mm², fracture toughness is 1.0MPa / m 2The visible light transmittance of 0.6mm thick microcrystalline glass at a wavelength of 300-780nm is 91%, and the haze is less than 0.09.

[0049] At this time, the impact of a 120g falling ball with a thickness of 0.6mm for the microcrystalline glass is less than 0.5m, and the four-point bending strength is 385MPa.

[0050] The microcrystalline glass was chemically strengthened using the following strengthening process: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h. The surface compressive stress was measured to be 460Mpa, the CS50 was greater than 170MPa, the DOL was 152μm, the tensile stress density line was greater than 40000MPa / mm, the impact of a 120g falling ball on 0.6mm thick glass could reach 1.4m, and the four-point bending strength was 710MPa.

[0051] Example 5

[0052] Raw materials (wt%): 54% SiO2; 18% Al2O3; 7% MgO; 4% Li2O; 4.3% ZrO2; 0.5% TiO2; 1.5% Na2O; 3% Y2O3; 0.5% P2O5; 0.5% B2O3; 0.1% Sb2O3; 1.5% ZnO; 0.1% K2O; 4% Ta2O5; 1% HfO2; Accurately weigh various raw materials according to the designed glass composition, mix the batch materials thoroughly and stir them evenly, then put them into a platinum crucible and melt them at 1580℃ for 24h, after casting and forming, annealing treatment at 600℃ for 5h and cooling with the furnace, the heat treatment process is as follows: nucleation temperature 690℃, nucleation time 8h, crystallization temperature 840℃, crystallization time 1h, after the heat treatment, cooling with the furnace to obtain microcrystalline glass.

[0053] The main crystal phase of the obtained glass-ceramics is Mg 0.6 Al 1.2 Si 1.8 O6、MgAL2Si4O 12 , cordierite, elastic modulus is 89GPa, Vickers hardness is 825kgf / mm², fracture toughness is 1.0MPa / m 2 The transmittance of 0.6mm thick microcrystalline glass at 550nm is greater than 91%, and the haze is less than 0.18.

[0054] At this time, the impact of a 120g falling ball on the 0.6mm thick microcrystalline glass is less than 0.6m, and the four-point bending strength is 400MP.

[0055] The microcrystalline glass was chemically strengthened using the following strengthening process: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h. The surface compressive stress was measured to be 580Mpa, the CS50 was greater than 195MPa, the DOL was 178μm, the tensile stress density line was greater than 46000MPa / mm, the impact of a 120g falling ball on 0.6mm thick glass could reach 1.4m, and the four-point bending strength was 880MPa.

[0056] Example 6

[0057] Raw materials (wt%): 56% SiO2; 16% Al2O3; 9% MgO; 3% Li2O; 7% ZrO2; 1% TiO2; 1.5% Na2O; 0.5% Y2O3; 0.5% P2O5; 0.5% B2O3; 0.2% Sb2O3; 2.3% ZnO; 0.3% K2O; 2% Ta2O5; 0.2% HfO2; Accurately weigh various raw materials according to the designed glass composition, mix the batch materials thoroughly and stir them evenly, then put them into a platinum crucible and melt them at 1580℃ for 24h, after casting and forming, annealing treatment at 600℃ for 5h and cooling with the furnace, the heat treatment process is as follows: nucleation temperature 650℃, nucleation time 8h, crystallization temperature 770℃, crystallization time 1h, after the heat treatment, cooling with the furnace to obtain microcrystalline glass.

[0058] The main crystal phases of the obtained microcrystalline glass are cordierite, MgAl2Si4O 12 Mg 0.6 Al 1.2 Si 1.8 O6、Mg 0.2 Zr 0.8 O 1.8, The elastic modulus is 90GPa, the Vickers hardness is 815kgf / mm², and the fracture toughness is 1.0MPa / m 2 The transmittance of 0.6mm thick microcrystalline glass at 550nm wavelength is greater than 91%, and the haze is less than 0.12.

[0059] At this time, the impact of a 120g falling ball on the microcrystalline glass with a thickness of 0.6mm is less than 0.6m, and the four-point bending strength is 405MPa.

[0060] The microcrystalline glass was chemically strengthened using the following strengthening process: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h. The surface compressive stress was measured to be 530MPa, CS50 was greater than 176MPa, DOL was 150μm, tensile stress density line was greater than 42000MPa / mm, 120g falling ball impact resistance for 0.6mm thick glass could reach 1.2m, and the four-point bending strength was 780MPa.

[0061] Example 7

[0062] Raw materials (wt%): 59% SiO2; 20% Al2O3; 7% MgO; 2.4% Li2O; 4.5% ZrO2; 2% TiO2; 1% Na2O; 1.2% Y2O3; 0.2% P2O5; 0.2% B2O3; 0.2% Sb2O3; 0.5% ZnO; 1.5% Ta2O5; 0.2% HfO2; Accurately weigh various raw materials according to the designed glass composition, mix the batch materials thoroughly and stir them evenly, then put them into a platinum crucible and melt them at 1580℃ for 24h, after casting and forming, annealing treatment at 600℃ for 5h and cooling with the furnace, the heat treatment process is as follows: nucleation temperature 680℃, nucleation time 8h, crystallization temperature 830℃, crystallization time 1h, after the heat treatment, cooling with the furnace to obtain microcrystalline glass.

[0063] The main crystal phases of the obtained microcrystalline glass are cordierite and Mg 0.6 Al 1.2 Si 1.8 O6、MgAL2Si4O 12 , Li x Al x Si 3-x O6, elastic modulus is 91GPa, Vickers hardness is 800kgf / mm², fracture toughness is 1.02MPa / m 2 The transmittance of 0.6mm thick microcrystalline glass at 550nm is greater than 91%, and the haze is less than 0.16.

[0064] At this time, the impact of a 120g falling ball at a thickness of 0.6mm for the microcrystalline glass is less than 0.5m, and the four-point bending strength is 400MPa.

[0065] The microcrystalline glass was chemically strengthened using the following strengthening process: 40% NaNO3+60% KNO3 molten salt ion exchange at 500℃ for 8h. The surface compressive stress was measured to be 470Mpa, the CS50 was greater than 170MPa, the DOL was 158μm, the tensile stress density line was greater than 41000MPa / mm, the impact of a 120g falling ball on 0.6mm thick glass could reach 1.2m, and the four-point bending strength was 815MPa.

[0066] Example 8

[0067] Raw materials (wt%): 64% SiO2; 16% Al2O3; 5% MgO; 3.5% Li2O; 4% ZrO2; 1.5% TiO2; 0.5% Na2O; 0.2% Y2O3; 0.3% P2O5; 0.2% B2O3; 0.3% Sb2O3; 1.5% ZnO; 2.5% Ta2O5; 0.5% HfO2; Accurately weigh various raw materials according to the designed glass composition, mix the batch materials thoroughly and stir them evenly, then put them into a platinum crucible and melt them at 1580℃ for 24h, after casting and forming, annealing treatment at 600℃ for 5h and cooling with the furnace, the heat treatment process is as follows: nucleation temperature 660℃, nucleation time 10h, crystallization temperature 810℃, crystallization time 1h, after the heat treatment, cooling with the furnace to obtain microcrystalline glass.

[0068] The main crystal phases of the obtained microcrystalline glass are spodumene and Li x Al x Si 3-x O6, elastic modulus is 88GPa, Vickers hardness is 795kgf / mm², fracture toughness is 1.01MPa / m 2 The transmittance of 0.6mm thick microcrystalline glass at 550nm is greater than 91%, and the haze is less than 0.17.

[0069] At this time, the impact of a 120g falling ball at a thickness of 0.6mm for the microcrystalline glass is less than 0.5m, and the four-point bending strength is 390MPa.

[0070] The microcrystalline glass was chemically strengthened using the following strengthening process: 40% NaNO3 + 60% KNO3 molten salt ion exchange at 500℃ for 8h. The surface compressive stress was measured to be 470Mpa, the CS50 was greater than 178MPa, the DOL was 158μm, the tensile stress density line was greater than 41000MPa / mm, the impact of a 120g falling ball on 0.6mm thick glass could reach 1.2m, and the four-point bending strength was 780MPa.

Claims

1. A magnesium aluminum silicon transparent glass-ceramic, characterized in that: According to mass percentage, its composition content is as follows: 45-68% SiO2, 16-35% Al2O3, 5-15% MgO, 0.2-6% ZnO, 0.1-4% B2O3, 1.5-7% Li2O, 0.5-5% Na2O, 0-4% K2O, 0.1-5% TiO2, 2-8% ZrO2, 0.1-4% P2O5, 0.1-6% Y2O3, 0.1-2% HfO2, 0.1-5% Ta2O5, 0.1~1.5% La2O3 and 0.1-0.5% Sb2O3, among which (MgO+ZnO+Y2O3) / (SiO 2+ The mass ratio of Al2O3) is 0.075-0.40, the crystallinity of the microcrystalline glass is ≥65%, and its crystal phase includes cordierite, Mg 0.6 Al 1.2 Si 1.8 O6、MgAL2Si4O 12 , spodumene, Li x Al x Si 3-x At least one of O6; its Vickers hardness is greater than 780kgf / mm²; fracture toughness is greater than 1.0MPa / m 2 ; Elastic modulus is greater than 88Gpa; At a thickness of 0.6mm, its transmittance in the visible light wavelength range is ≥91%, and the haze is less than 0.

2.

2. The magnesium aluminum silicon transparent glass-ceramic according to claim 1, characterized in that: The mass ratio of MgO / (SiO2+Al2O3) is 0.06~0.

28.

3. The magnesium aluminum silicon transparent glass-ceramic according to claim 1, characterized in that: (Li2O+Na2O+K2O) / (SiO 2+ The mass ratio of Al2O3 is 0.025~0.

15.

4. The magnesium aluminum silicon transparent glass-ceramic according to claim 1, characterized in that: (ZrO2+TiO2+Ta2O5) / (SiO 2+ The mass ratio of Al2O3 is 0.035~0.

167.

5. The magnesium aluminum silicon transparent glass-ceramic according to claim 4, characterized in that: The mass ratio of TiO2 / (ZrO2+Ta2O5) is 0.2-2.

6. A method for preparing a magnesium-aluminum-silicon transparent glass-ceramics according to any one of claims 1 to 5, characterized in that: The following steps are involved: Raw material preparation, mixing, melting, cooling, overflow molding or float molding, annealing treatment, crystallization treatment, wherein the melting temperature is 1520-1580°C, and the melting time is 10 hours; the annealing temperature is 550-650°C, and the time is 4 hours; the raw material composition is: 45-68% SiO2, 16-35% Al2O3, 5-15% MgO, 0.2-6% ZnO, 0.1-4% B2O3, 1.5-7% Li2O, 0.5-5% Na2O, 0-4% K2O, 0.1-5% TiO2, 2-8% ZrO2, 0.1-4% P2O5, 0.1-6% Y2O3, 0.1-2% HfO2, 0.1-5% Ta2O5, 0.1~1.5% La2O3 and 0.1-0.5% Sb2O3.

7. The method for preparing magnesium aluminum silicon transparent glass-ceramics according to claim 6, characterized in that: The crystallization treatment is divided into two stages. The temperature of the first stage is 630-720°C and the time is 4-10h; the temperature of the second stage is 750-920°C and the time is 1-2h.

8. A reinforced magnesium aluminum silicon transparent glass-ceramic, characterized in that: The strengthened glass-ceramics is obtained by chemically strengthening the glass-ceramics according to claim 1; Its surface compressive stress is greater than 400Mpa, CS50 is greater than 170MPa, DOL is greater than 150 microns, and the tensile stress density line is greater than 40000MPa / mm; at a thickness of 0.6mm, the entire face of the 2.5D sample falls from a height of 1.8m without damage, the height of a 120g ball drop is greater than 1.2m, and the four-point bending strength is greater than 700MPa.

Citation Information

Patent Citations

  • Transparent high-hardness magnesium-aluminum-silicon microcrystalline glass and preparation method thereof

    CN113735450A